2006
DOI: 10.1007/s10798-006-9002-4
|View full text |Cite
|
Sign up to set email alerts
|

Sparking self-sustained learning: report on a design experiment to build technological fluency and bridge divides

Abstract: In this article we report assessment results from two studies in an ongoing design experiment intended to provide a single school system with a sequence of secondary school level (ages 14-18) computer technology courses. In our first study, we share data on students' learning as a function of the required introductory course and their pre-course history of technological experience. In order to go beyond traditional assessments of learning we assessed two aspects of students' ''learning ecologies'': their use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
11

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
0
24
0
11
Order By: Relevance
“…Few parents of students in the public schools hold jobs that require a high level of technical knowledge. In one recent sample of almost 100 Bermuda students, we found that over half of fathers worked in trades such as carpentry or painting, and while about 60% of mothers worked in offi ce settings, none were in a profession that involved the computer industry [Barron, Martin, & Roberts, 2006]. Most of the students in this study reported that they knew more than their parents about computers and that they frequently teach them, rather than the other way around.…”
Section: Example 1: Classroom Learning Sparks the Creation Of New Leamentioning
confidence: 56%
See 2 more Smart Citations
“…Few parents of students in the public schools hold jobs that require a high level of technical knowledge. In one recent sample of almost 100 Bermuda students, we found that over half of fathers worked in trades such as carpentry or painting, and while about 60% of mothers worked in offi ce settings, none were in a profession that involved the computer industry [Barron, Martin, & Roberts, 2006]. Most of the students in this study reported that they knew more than their parents about computers and that they frequently teach them, rather than the other way around.…”
Section: Example 1: Classroom Learning Sparks the Creation Of New Leamentioning
confidence: 56%
“…One of these projects was an international collaboration between a research group at Stanford and teachers and education ministry offi cials in the country of Bermuda [Barron, Martin & Roberts, 2006]. The project was a design experiment [Brown, 1992] that involved curriculum Interest and Self-Sustained Learning 203 Human Development 2006;49:193-224 development, professional development, and assessment of student learning (for more details, please see http://bermuda.stanford.edu/).…”
Section: Analytical Perspective and Settings For Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the term fluency as proposed by Papert and Resnick (1995), when discussing technological fluency in parallel to being fluent with a particular language, is more adequate to capture the specificities of the mathematical and technological activity that takes place within the competition SUB14. Barron, Martin and Roberts (2007) argue that "fluency is an appropriate notion to describe the ability to reformulate knowledge, express oneself creatively and appropriately, and to produce and generate information (rather than simply comprehend it)" (p. 83). As it happens with language and linguistic fluency, technological tools are an extension of the individual who is technologically fluent, so this kind of fluency is about being able to think and express oneself by means of a dialect, meaning that concepts flow from our brain and out of our mouth.…”
Section: Techno-mathematical Fluency In Problem Solving-and-expressingmentioning
confidence: 99%
“…This case illustrates the way in which GeoGebra is given the role of a tool-to-create-with: 1) in the first solution, it is the construction activity that enables apprehending the relationships between the lengths of the several squares; 2) in the second one, the robust construction, enhanced by the dynamic variation of the objects, leads to a wider perspective of the problem posed, extending several of its conditions and allowing a generalization. The digital constructions become part of the process and of the solution itself, in that they trigger powerful mathematical ideas that she uses to reformulate or create new ways of knowing (Barron, Martin, & Roberts, 2007). Jessica's effective uses of GeoGebra are linked to the way in which the constructions bring forth the conceptual structures underlying the process of obtaining and presenting the solution.…”
Section: The Evidence Of Techno-mathematical Fluencymentioning
confidence: 99%